Gender and development - Pajvančić-Cizelj Ana (Temida)
Author analyses theories of social development and dominant development practice (dominant models of social development) from critical feminist perspective. The key problem of dominant development model is found to be an equation of social development with economic growth. Review of feminist theories of development from WID to GAD approach is given, and the author shows that these theories questioned economic growth theories by developing a concept of gender regimes which mediates distribution of economic benefit. From simple inclusion of women in development process, gender development theories moved to deeper investigation of these processes from gender perspective. In that manner, gender development theories became true critical theories which contribute to better conceptualization and practical planning of more human and sustainable development for society in general.